Synthesis of Functional Ceramic Supports by Ice Templating and Atomic Layer Deposition - Klotz, Michaela; Weber, Matthieu; Deville, Sylvain; Oison, Didier; Iatsunskyi, Igor; Coy, Emerson; Bechelany, Mikhael (Frontiers in Materials, 2018)
In this work, we report an innovative route for the manufacturing of functional ceramic supports, by combining ice templating of yttria stabilized zirconia (YSZ) and atomic layer deposition (ALD) of Al2O3 processes. Ceramic YSZ monoliths are prepared using the ice-templating process, which is based on the controlled crystallization of water following a thermal gradient. Sublimation of the ice and the sintering of the material reveal the straight micrometer sized pores shaped by the ice crystal growth. The high temperature sintering allows for the ceramic materials to present excellent mechanical strength and porosities of 67%. Next, the conformality benefit of ALD is used to deposit an alumina coating at the surface of the YSZ pores, in order to obtain a functional material. The Al2O3 thin films obtained by ALD are 100 nm thick and conformally deposited within the macroporous ceramic supports, as shown by SEM and EDS analysis. Mercury intrusion experiments revealed a reduction of the entrance pore diameter, in line with the growth per cycle of 2 Å of the ALD process. In addition to the manufacture of the innovative ceramic nanomaterials, this article also describes the fine characterization of the coatings obtained using mercury intrusion, SEM and XRD analysis.